Lesbian erasure in contemporary reactions to the life of Vita Sackville-West - Vega, Beatriz (The Grove - Working Papers on English Studies, 2025)
This article focuses on the biographical facts that point to the lesbianism of British author Vita Sackville-West in order to identify and question some of the modern approaches that define her sexuality in ambiguous terms that, as I shall agree, have led to a lesbian erasure based on heterosexist views. To achieve that, I will be comparing the conclusions reached by other people who have looked at Sackville-West’s literary and social legacy with her own testimonies and those of others close to her. I will analyse and debate some quotes from blogs and webpages devoted to Sackville-West, primarily using feminist theory in order to reveal and clarify the heterosexist elements of some reactions to her life. The fragments from letters and diaries are compiled in Victoria Glendinning’s biography Vita: The Life of Vita Sackville-West (1983) and in Nigel Nicolson’s Portrait of a Marriage (1973), both of which I will refer to throughout the article.